ASSESSMENT OF COGNITIVE STATUS IN ELDERLY PERSONS IN THE COMMUNITY - Zivanovic, Srdjan (PONS - medicinski časopis, 2023)
Introduction. Aging is characterized by the loss of abilities in the psychological and physical sense. Detailed assessment of cognitive status may enable early identification of high-risk patients who are candidates for dementia. The aim of this research was to examine the cognitive status of elderly people over 65 years of age living in the community and potential risk factors that contribute to the onset of dementia. Material and methods. The research was designed according to the principle of a cross-sectional study. The research used a general questionnaire, subjective and objective assessment of respondents, Mini Kog assessment. The χ2 square test was used for statistical tests, and Pearson’s correlation analysis was used for association analysis. The usual value of p<0.05 was taken as the level of statistical significance. Results. Females (80.2%) had better cognitive status than males (84.6%) (x2=0.189; p=0.664). Respondents with the lowest level of education (primary school) had a worse cognitive status (23.5%) compared to 13.3% of respondents with an intermediate level of education (x2=9.139; p=0.010). 8.8% of respondents who socialize with friends had a good cognitive score compared to 0% of respondents with a good cognitive score who do not socialize with friends (x2=18.243; p=0.000), also, the cognitive status was worse in those respondents who used different aids (75%) versus 17% of those who do not use different aids for their functional mobility (x2=8.832; p=0.003). Conclusion. Dementia is present in a high percentage among elderly people. The level of education, social interaction with friends and the use of aids are potential risk factors for the onset of dementia. Key words: age, instruments, cognitive assessment, dementia, elderly people.